Effects of supplementation of n-3 polyunsaturated fatty acids on renal functions in diabetes patients:a meta-analysis - ZHOU Qian-ying; WU Qiong; ZOU Qin; CUI Yi (Linchuang shenzangbing zazhi)
Objective We performed a meta-analysis to systematically evaluate the impact of n-3 polyunsaturated fatty acids(n-3 PUFAs)supplementation on renal functions in diabetes patients,and to provide theoretical basis for chronic diabetic disease management.Methods We searched Pubmed,Cochrane Library,Embase,and three major Chinese biomedical databases(CNKI,VIP and WANGFANG)for randomized controlled trials(RCTs)to examine the effects of n-3 PUFAs on renal function in diabetes patients,published before August 31,2018.Quality assessment and data extraction were performed,and RevMan 5.3 software was used for the Meta-analysis.Results We included 11 RCTs representing 614 patients with diabetes in this meta-analysis.The meta-analysis showed that,n-3 PUFAs supplementation significantly reduced urinary albumin excretion[MD=-2.65,95% CI(-4.67,-0.62),P=0.01]and serum creatinine level[MD=-2.60,95% CI(-4.98,-0.22),P=0.03],and delayed creatinine clearance decrease[MD=9.23,95% CI(4.37,14.09),P=0.0002].However,n-3 PUFAs supplementation failed to decrease urea nitrogen,uric acid and glomerular filtration rate.Conclusions In diabetes patients,n-3 PUFAs supplementation provides beneficial effects on urinary albumin excretion,serum creatinine and creatinine clearance,but has no obvious improvement effects on urea nitrogen,uric acid and glomerular filtration rate.